The Beneficial Role of Auricular Point Pressure in Insomnia and Anxiety in Isolated COVID-19 Patients. (15th July 2021) - Luo, Yueming; Ling, Chuanren; Liu, Yangchen; Deng, Chong; Waaga-Gasser, Ana Maria; Chen, Minggui; He, Zehui; Chen, Erhui; Wei, Lin; Luo, Shimiao; Gong, Xiaozhen; Ye, Hong; et al.
Abstract : Background . Coronavirus disease 2019 (COVID-19) causes psychological distress and can have a negative impact on the general mental health and rehabilitation in affected patients under currently implemented isolation guidelines. Auricular point pressure (APP) as well-established technique in traditional Chinese medicine may help to relieve sleep disturbance and anxiety in COVID-19 patients. Methods . During the early phase of the epidemic/pandemic, patients were enrolled in this study (02/2020 until 03/2020 n = 84). They were strictly isolated on specific wards at the Hubei Provincial Hospital of Integrated Chinese and Western Medicine in Hubei. The retrospective cohort study design included two groups. Group A patients were treated with an auricular point pressure (APP) in addition to standard intensive care medicine while Group B participants (No-APP) received routine nursing measures alone. Treatment outcome was measured using the St. Mary's Hospital Sleep Questionnaire (SMH) Score and the 7-Item Generalized Anxiety Disorder Scale (GAD-7). Both scores were measured in each patient at baseline and on the discharge day. Results . The SMH score and sleep status changed in APP patients at the end of the treatment period when compared with No-APP patients (P < 0.01 ). APP-treated patients demonstrated lower GAD-7 scores than No-APP controls (P < 0.01 ). Further, no significant differences in safety or adverse events between the APP and No-APP groups were observed. Conclusion . The results from our snapshot study during the early phase of the SARS-CoV-2 epidemic/pandemic suggest that auricular point pressure could be a simple and effective tool to relieve insomnia and situational anxiety in hospitalized patients suffering from COVID-19 and kept under disconcerting conditions of isolation.